2019
DOI: 10.1136/gpsych-2019-100051
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of repetitive transcranial magnetic stimulation for generalised anxiety disorder: A meta-analysis

Abstract: BackgroundPharmacological and conventional non-pharmacological treatments are only moderately effective in treating generalised anxiety disorder (GAD). Recently, repetitive transcranial magnetic stimulation (rTMS) has attracted interest because of its potential therapeutic value.AimTo investigate the efficacy and safety of rTMS treatment for GAD.MethodsLiterature studies published in English or Chinese were screened in 10 electronic databases up to 5 December 2018. The included studies’ bias risk was assessed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 28 publications
3
11
0
Order By: Relevance
“…Crucially, the effect was not likely to have been influenced by publication or reporting bias. In line with previous systematic reviews 35 and meta-analyses, 72,73 we also acknowledge the limitations of these results, which are based on a restricted sample of studies but a relatively large pool of patients (318 in total). We included only representative moderators in our moderation analyses because of the small number of studies in our analysis.…”
Section: Main Effect Of Noninvasive Brain Stimulation On Anxiety and Moderation Analysissupporting
confidence: 77%
See 2 more Smart Citations
“…Crucially, the effect was not likely to have been influenced by publication or reporting bias. In line with previous systematic reviews 35 and meta-analyses, 72,73 we also acknowledge the limitations of these results, which are based on a restricted sample of studies but a relatively large pool of patients (318 in total). We included only representative moderators in our moderation analyses because of the small number of studies in our analysis.…”
Section: Main Effect Of Noninvasive Brain Stimulation On Anxiety and Moderation Analysissupporting
confidence: 77%
“…However, so far they have included single-case studies and protocols without a control condition, providing an overview of the state of the art, but without cumulatively quantifying the results. To our knowledge, 3 meta-analyses [71][72][73] have investigated the efficacy of rTMS from a quantitative perspective. Cui and colleagues 72 investigated the efficacy of rTMS in treating generalized anxiety disorder.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Crucially, the effect was not likely influenced by publication or reporting bias. In line with previous systematic reviews 34 and meta-analyses 71, 72 , we also acknowledge the limitation of the present results, which are based on a restricted sample of studies, but a relatively big pool of patients (318 in total).…”
Section: Discussionsupporting
confidence: 83%
“…It has been shown that rTMS is promising treatment option for many neuropsychiatric conditions like depression, 2,24,25 OCD, 28 BD, 36,37 negative symptoms 29 and auditory hallucinations 30,31 in schizophrenia, addiction,s [33][34][35] anxiety and anxiety related disorders, [39][40][41] fibromyalgia, 44,45 chronic pain, 42,43 and dementia/Alzheimer's disease. [46][47][48][49] It is also very important that many studies reported that rTMS causes significant improvement of cognition.…”
Section: Resultsmentioning
confidence: 99%